Influence of temperature and relative humidity of air and the determination of the trophic state in Tillandsia stricta Lindl. (Bromeliaceae) in State park of Anchieta Island - G. Suhogusoff, Valentin; Piliackas, José Mauricio; de Castro, Isac; Barbosa, José Marcos (O Mundo da Saúde, 2008)
Bromeliaceae Tillandsia stricta is a vascular epiphyte characterized as an atmospheric species due to its capacity of absorbing the nutrients it needs directly from the air through its leaves. This bromeliad is distributed in abundance along some phorophytes found in the State Park of Anchieta Island in Ubatuba (SP), being rare in others. In this work we tried to establish the existence of possible differences regarding temperature and relative humidity of air in three places (Praia do Presídio, Trilha do Saco Grande e Praia das Palmas), where this species presents irregular distribution. Besides, the trophic state was evaluated through the analysis of macro and micronutrients present in the leaves. We found significant differences of relative humidity of air that are greater in Praia do Presídio and Saco Grande and lesser in Praia das Palmas. As for the nutrients, in Praia do Presídio T. stricta presented higher concentrations of iron when compared to the other two places. The differences in these abiotic factors may explain the highest concentration of T. stricta individuals in Praia do Presídio.